Pengaruh Promosi dan Impulse Buying Terhadap Keputusan Pembelian pada Bunga Swalayan Sampang - Rynaldi Pratama Nur Maulana; Supriyono Supriyono (Jurnal Ekonomi, 2021)
The purpose of this study was to determine the effect of promotion and impulse buying on purchasing decisions at Bunga Swalayan. This research is a quantitative research that uses a questionnaire as a data collection method. With a population of all consumers who make purchases at Bunga Swalayan Sampang. The sample in this study amounted to 50 respondents using accidental sampling technique. The data used are primary and secondary data. While the analysis used is Partial Least Square (PLS). The results in this study indicate that 1) promotion has a positive effect on purchasing decisions at Bunga Swalayan Sampang, 2) impulse buying has a positive effect on purchasing decisions at Bunga Swalayan Sampang.